تلقي الناقد محمد عزّام للمنهج البنيوي التكويني "فضاء النّص الروائي" أنموذجا - لطرش, يوسف; حمداوي, فهيمة (جامعة الوادي - university of Eloued, 2022)
وقفنا من خلال دراستنا هذه المعنونة بتلقي الناقد "محمد عزّام" للمنهج البنيوي التكويني -فضاء النص الروائي- أنموذجا على أهم الجوانب النظرية الخاصة بالمنهج البنيوي التكويني والمتمثلة في الجهاز المفاهيمي والاصطلاحي وأهم الرواد،أمّا الجانب التطبيقي فكان دراسة في مجال "نقد النقد" باعتماد خطاب التحقيق والمراد منه اختبار الصحة من خلال دراستنا للكتاب النقدي والمعنون بفضاء النّص الروائي مقاربة بنيوية تكوينية للناقد "محمد عزّام" مبرزين أهم المفاهيم والمصطلحات التي اعتمدها الناقد عزّام في دراسته لروايات الكاتب السوري نبيل سليمان. Abstract Through our study, entitled "Receiving the Critic "Mohammed Azzam" of the structural-formative approach - the space of the narrative text- a model on the most important theoretical aspects of the structural-formative approach represented in the conceptual and idiomatic apparatus and the most important pioneers, while the applied side was a study in V. The field of "Criticism of Criticism" by adopting the discourse of investigation, and it is intended to test the correctness through our study of the critical book entitled in the space of the fictional text. A structural and formative approach to the critic "Muhammad Azzam", highlighting the most important concepts and terminology adopted by the critic Azzam in his study of the novels of the Syrian writer Nabil Suleiman Key words: Seeing the world, meaningful structure, possible awareness, object awareness, understanding, interpretation
Critic Muhammad Azzam's Reception of the Structural-Formative Approach "The Space of the Narrative Text" a model
مقال
Keywords: رؤية العالم،البنية الدالة،الوعي الممكن،الوعي الكائن،الفهم، التفسير; Seeing the world, meaningful structure, possible awareness, object awareness, understanding, interpretation